Integrative Assessment of Cardiopulmonary Fitness Using Cardiopulmonary Exercise Test With Supine Bicycle Echocardiography in Patients Presenting Dyspnea - Jiesuck Park; Houng‐Beom Ahn; Hyejung Choi; Hong‐Mi Choi; In‐Chang Hwang; Yeonyee E. Yoon; Goo‐Yeong Cho (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Cardiopulmonary exercise test (CPET) with supine bicycle echocardiography (SBE) enables comprehensive physiologic assessment during exercise. We characterized cardiopulmonary fitness by integrating CPET‐SBE parameters and evaluated its prognostic value in patients presenting with dyspnea. Methods and Results We retrospectively reviewed 473 consecutive patients who underwent CPET‐SBE for dyspnea evaluation. A dimensionality reduction process was applied, transforming 24 clinical and CPET‐SBE parameters into a 2‐dimensional feature map, followed by patient clustering based on the data distribution. Clinical and exercise features were compared among the clusters in addition to the 5‐year risk of clinical outcome (a composite of cardiovascular death and heart failure hospitalization). Maximum exercise effort (R >1) was achieved in 95% of cases. Through dimensionality reduction, 3 patient clusters were derived: Group 1 (n=157), 2 (n=104), and 3 (n=212). Median age and female proportion increased from Group 1 to 2, and 3, although resting echocardiography parameters showed no significant abnormalities among the groups. There was a worsening trend in the exercise response from Group 1 to 2 and 3, including left ventricular diastolic function, oxygen consumption, and ventilatory efficiency. During follow‐up (median 6.0 [1.6–10.4] years), clinical outcome increased from Group 1 to 2 and 3 (5‐year rate 3.7% versus 7.0% versus 13.0%, respectively; log‐rank P=0.02), with higher risk in Group 2 (hazard ratio, 1.94 [95% CI, 0.52–7.22]) and Group 3 (3.92 [1.34–11.42]) compared with Group 1. Conclusions Comprehensive evaluation using CPET‐SBE can reveal distinct characteristics of cardiopulmonary fitness in patients presenting with dyspnea, potentially enhancing outcome prediction.